The false allure of fast lures - Yigal Attali; Maya Bar-Hillel (Judgment and Decision Making, 2020)
The Cognitive Reflection Test (CRT) allegedly measures the tendency to override the prepotent incorrect answers to some special problems, and to engage in further reflection. A growing literature suggests that the CRT is a powerful predictor of performance in a wide range of tasks. This research has mostly glossed over the fact that the CRT is composed of math problems. The purpose of this paper is to investigate whether numerical CRT items do indeed call upon more than is required by standard math problems, and whether the latter predict performance in other tasks as well as the CRT. In Study 1 we selected from a bank of standard math problems items that, like CRT items, have a fast lure, as well as others which do not. A 1-factor model was the best supported measurement model for the underlying abilities required by all three item types. Moreover, the quality of all these items -- CRT and math problems alike -- as predictors of performance on a set of choice and reasoning tasks did not depend on whether or not they had a fast lure, but rather only on their quality as math items. In other words, CRT items seem not to be a ``special'' category of math problems, although they are quite excellent ones. Study 2 replicated these results with a different population and a different set of math problems.